STUDI EKSPERIMEN KUAT TEKAN BETON BERDASARKAN URUTAN DAN WAKTU PERPUTARAN PENCAMPURAN MATERIAL PENYUSUN BETON DENGAN ADUKAN MENGGUNAKAN MESIN MOLEN - Hermiyati, Rosita; Mungok, Chrisna Djaya; Supriadi, Asep (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
This paperpresents theexperimentalresults ofthe compressive strength ofconcretebased onthe order ofmixingandmixingturnover timeconstituentmaterialsof concretewithmortarusingmolenmachine. Specimensmade​​cylindricalwithsizeØ15cmheight30cm. Aims to determinethe extent ofthe effectofthe orderandstirringturnaroundtimewhenmixingconcreteformingmaterialormaterialof compressive strengthof concreteproduced.Jobmixformulausingthe ACImethod. From the researchthat has beendone, the order ofmixingcement, sand, gravel, waterproducethe finalcompressive strengthisbest whencomparedwithother variationswithan average of30.01MPaor33.38% and atime of 11minutes28secondswith thenumber of180.48turnaroundturnaroundtimes, so thatis greater thanthequality ofthe plan. Althoughvariations ofcement, gravel, sand, waterproducesthe smallestcompressive strengthwhen comparedto theother variations, withan averagecompressive strengthof23.87MPaor6.08%andtime17minutes35secondswith aturnover of277.6timesthe amount ofturnover,so lessonthe quality ofthe plan, but itcan still bedone atthe field. The longerstirring, it does not meanthe better theresults produced, andthe soonerdonedoes notmeanthe result is badsoyou shouldalsonote thetime ofturnover andtheturnovernumberwith atime of 13minutes63seconds, orby calculating therotationvelocity ofapproximately218.08times.   Keywords: mixingorder, time, Turnover, compressive strength, PPCCement.